Mapping The Potential of Interactive Drama Techniques in the South African Workplace: Playing is not always about making a Play - Bruwer, Frances Charlize (Stellenbosch : Stellenbosch University, 2026)
Thesis (MA)--Stellenbosch University, 2026.